The structural model of emotional divorce based on the dark triad traits of personality and conflict resolution styles with the mediation of marital boredom - Sadeghkhani , Marjan; Emamipour , Susan; Mirhashemi , Malek (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of modeling the structural equations of emotional divorce based on dark personality traits and conflict resolution styles with the mediation of marital dissatisfaction. Method: The research method was descriptive correlation type based on structural equations. The statistical population of this research consisted of all married women in the age group of 25-50 years of Tehran Azad University, Yadgar Imam (RA), Abol Fattouh Razi (Mothers) and North Tehran units in the first half of 2021, which was available online through the sampling method. (due to the spread of the corona virus) were chosen. The research tools were Gottman's Emotional Divorce Questionnaire (1994), Dark Triangle of Personality Johnson and Webster (2010), Rahim's Conflict Resolution Styles (1983) and Pines Marital Boredom (1996). Analyzes were done using SPSS and AMOS software. Result: The results of structural equation modeling showed that the assumed research model fits the experimental data (RMSEA=0.063). A significant relationship was observed between Machiavellian trait and emotional divorce (β=0.149) and between constructive style (β=0.441) and non-constructive style (β=0.264) with emotional divorce. The coefficient of the indirect path of marital boredom was significant in the relationship between narcissistic trait (P = 0.007) and constructive conflict resolution styles (P = 0.043) with the dependent variable of emotional divorce, but the mediating role of marital boredom in the relationship between non- constructive was not confirmed by emotional divorce (P = 0.536). Conclusion: Dark traits and constructive conflict resolution styles, in addition to having a direct effect on emotional divorce, can indirectly affect marital boredom.